A Constitutive Model of Clay Considering Structural Failure - Zhou, Biaohe; Tang, Bin; Kang, Jiashuai (Frontiers in Materials, 2021)
Due to the different material composition and deposition conditions, the undisturbed clay presents different degree of structure. Because of the existence of structure, the undisturbed clay has structural yield stress. When the stress level exceeds the structural yield stress, the stress-strain relation of undisturbed clay has typical softening characteristics. To explore the constitutive relation of undisturbed soil, triaxial consolidation and drainage tests were carried out on undisturbed and remolded soils of structural clay in Zhanjiang Formation in China, and the stress-strain relations under different confining pressures were obtained. By analyzing the structural failure process of undisturbed clay, Weibull distribution was introduced to describe the strength distribution of each point in undisturbed clay, and the structural failure coefficient of undisturbed clay was established during the loading process. Based on the elastic theory and structural failure coefficient, a constitutive model considering the structural failure of clay was proposed, and the method to determine the model parameters was given. The model was used to simulate the experimental data in this paper and the reference, and the validity of the model was verified. The results show that the model can well simulate the softening effect of structural clay during loading.